Clinical Presentation and Surgical Outcomes of Brain Abscesses. A Cross-Sectional Clinical Study from a Tertiary Care Hospital - SAUD AHMED; MUHAMAAD NAEEM UR REHMAN; HASSAAN SHARIF (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Brain abscess remains a potentially fatal neurological emergency in underdeveloped settings. Timely surgical intervention significantly improves outcome, provided diagnosis is prompt. The purpose of this study is to ascertain the clinical presentation, imaging, microbiological profile and surgical outcome of brain abscess in a tertiary center. Methodology: A cross sectional clinical study was conducted at Department of Neurosurgery, Aziz Fatimah Hospital Faisalabad, Pakistan between January 2024 to December 2024. Fifty six patients with brain abscess according to clinical and radiological criteria were included. Abscess size, location and clinical status dictated whether patients had burr hole aspiration or craniotomy. Data were recorded and analyzed on pre and postoperative clinical evaluations, radiological findings, microbiology reports and outcomes. Results: The mean age of the patients was 34.8 ± 13.2 years; 2.2 male: female. The most common presenting symptoms were headache (82.1%), fever (67.9%), and altered consciousness (44.6%). Most commonly involved were the frontal lobe (39.3%) and temporal lobe (23.2%). The most common source was otogenic and hematogenous spread. The predominant isolates were Streptococcus spp. and Staphylococcus aureus. In 42 patients, Burr hole aspiration was performed and in 14 patients, craniotomy. In 85.7% of cases postoperative improvement was noted. Complications included residual neurological deficits (8.9%), seizures (10.7%) and in- hospital mortality rate was 5.3%. Conclusion: Brain abscess remains a clinical problem in developing healthcare system. Timely identification, optimized antimicrobial therapy along with appropriate surgical management has a favorable outcome. Optimal recovery and lowering of morbidity and mortality require a multidisciplinary approach.